"It's Awful When We Get It Wrong": An Exploratory Qualitative Study of Vocational Rehabilitation Counselors' Perspectives on Suicide. (September 2020) - Lund, Emily M.; Schultz, Jared C.; Thomas, Katie B.; Nadorff, Michael R.; Chowdhury, Dalia; Galbraith, Kate
Despite the high prevalence of suicide among people with disabilities, little research has explored suicide in the context of the vocational rehabilitation (VR) system. We analyzed the responses of 27 VR counselors who responded to an open-ended qualitative prompt regarding their experiences with suicide training and competency. Key themes included a desire for more training on suicide and the experience of seeking and receiving suicide training and experience outside of VR. Responses also underscored the heavy emotional impact of working with suicidal clients, especially when one feels unprepared to do so. These results suggest that it is important to provide VR counselors with resources and training for addressing suicide in their client populations.